A user-generated content analysis of tourists at wildlife tourism attractions - Kredens, Claire; Vogt, Christine A. (Frontiers in Sustainable Tourism, 2023)
Introduction Captive wildlife tourism is an increasingly complex subsector of ecotourism due to the varying degrees of care given to the animals, interpretation or education provided, and tourist expectations of potential interaction with the animals. Two recent tourism trends are the growing wildlife tourism sphere of ecotourism and the increased use of social media in both marketing and for tourists to share their experiences. In scientific literature, the connection between social media and tourism was largely under-studied, and tourist behavior on Instagram after visiting wildlife tourism attractions (WTAs) has not been studied. Some researchers call for more tourism research using social media data created by tourists, called user-generated content (UGC), to understand tourist behaviors. Methods This netnographic study examines tourists who visited a WTAs by analyzing their post-visit photos and captions on Instagram through the lens of involvement theory to evaluate the strength of their connection to wildlife and conservation. Previous research indicated wildlife tourism can have extraordinary benefits to conservation and communities, but some WTAs, some of which are photo-prop tourism attractions where animals are handed over to tourists for close-contact selfies, produce negative impacts on individual animals and entire species due to illegal sourcing, improper care, human interaction, and habituation. Results Findings from this study suggest WTAs with good or excellent conservation and welfare practices were found to lead to more highly involved tourists, ultimately benefitting community investment, animal welfare, and conservation efforts via the flow of tourist dollars and spread of information on social media, the tourist changing their behavior, or all the aforementioned. Conversely, WTAs with negative conservation and welfare practices were found not to foster the same level of tourist involvement as their counterparts, often leading to more anthropocentric Instagram posts that do not spread conservation messaging or imply appropriate tourist-animal interactions. Discussion The implications from this research suggest that WTA management practices should move toward a model focusing on conservation-themed interpretation, education, and positive animal welfare for the improvement of conservation efforts within wildlife and eco-tourism. Such models should keep up with evolving sustainability, responsible, and regenerative practices adopted by the tourism and outdoor recreation industry.